The influence of class mobility on pain empathy among the wealthy in collectivist cultures: evidence from ERPs - Huang, Bingni; He, Jinwen; Wu, Xiaomin; Luo, Jiaxian; Zhang, Yanshan; Luo, Pinchao (Frontiers in Human Neuroscience, 2026)
IntroductionAs a privileged group within the social structure, the wealthy play a significant role in social philanthropy and public welfare initiatives, making their empathic capacity a subject of considerable interest. Previous research has found that wealthy individuals who have experienced upward class mobility paradoxically demonstrate reduced empathy toward the poor. However, these studies were predominantly conducted in individualistic cultural contexts, leaving the collectivist cultural perspective largely unexplored.MethodsThe present study employed a virtual-society paradigm to experimentally simulate class mobility in a collectivist context. Objective mobility direction (upward vs. horizontal) and subjective evaluation of mobility (positive vs. negative) were manipulated to construct four types of wealthy roles (upward-positive, upward-negative, horizontal-positive, horizontal-negative). Chinese university students from a collectivist cultural background were instructed to sequentially adopt each wealthy role and judge painful versus neutral pictures of the same low-status target, while event-related potentials (ERPs) were recorded.ResultsThe results revealed that in the early N2 component, under upward mobility conditions, pain stimuli elicited significantly smaller N2 amplitudes compared to neutral stimuli, while no significant difference was observed under horizontal mobility conditions. In positive evaluation conditions, pain stimuli evoked significantly smaller N2 amplitudes than neutral stimuli, whereas no significant difference emerged in negative evaluation conditions. For the late LPP component, pain stimuli consistently elicited significantly larger LPP amplitudes than neutral stimuli, regardless of either the objective direction of class mobility or subjective evaluation.DiscussionThese findings suggest that, within this simulated class-mobility context, upward mobility experiences and positive appraisal primarily influence early neural processing of the poor target’s pain, while later evaluative processing remains relatively stable. This study provides neural-level evidence for understanding how class mobility affects pain empathy among the wealthy in collectivist cultures, thereby enriching research on the relationship between social stratification and pain empathy.